Evaluation of Biofilm Formation in Klebsiella Pneumoniae and Antibiotic Resistance - Sara Hadi Jassim; Anfal Shakir Motib (Institute of Medico-legal Publications Pvt Ltd, 2021)
Biofilm are densely packed communities of germ cell (bacterial cells), that grow either on living or inertsurface, surround themselves with secreted polymers, the role of biofilm formation and development bybacteria has been suggested to be an important stage in the pathogenesis of numerous bacterial species.In this study klebsiella pneumoniae has been investigated to form biofilms and its relation to antibioticsresistant. The antibiotics which are used in this study are Ciprofloxacin (CIP) and Cefotaxime (CTX) becausemost of the isolates showed resistance to these antibiotics. The experiment was design to check the causeof UTI in the different types of patient by taking their urine as a specimen sample. Out of 160; 24 samplesshowed Klebsiella pneumoniae, which cause the urinary tract infection. The organisms were identifiedby the DNA isolation and checking with PCR using 16SrRNA. Antibiotic susceptibility for the differentgroups of antibiotic were done by using disk diffusion method against all Klebsiella pneumoniae isolates.Klebsiella pneumoniae are important infectious bacterium and become more dangerous with their capacityof multi-drug resistant. Therefore, there is need to find out alternate therapy to eradicate the infection of thisbacterium by reduce the formation of biofilm which may lead to decrease the antibiotics resistance.